If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(9n + -1) + 7(n + 6) = -69 Reorder the terms: 2(-1 + 9n) + 7(n + 6) = -69 (-1 * 2 + 9n * 2) + 7(n + 6) = -69 (-2 + 18n) + 7(n + 6) = -69 Reorder the terms: -2 + 18n + 7(6 + n) = -69 -2 + 18n + (6 * 7 + n * 7) = -69 -2 + 18n + (42 + 7n) = -69 Reorder the terms: -2 + 42 + 18n + 7n = -69 Combine like terms: -2 + 42 = 40 40 + 18n + 7n = -69 Combine like terms: 18n + 7n = 25n 40 + 25n = -69 Solving 40 + 25n = -69 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-40' to each side of the equation. 40 + -40 + 25n = -69 + -40 Combine like terms: 40 + -40 = 0 0 + 25n = -69 + -40 25n = -69 + -40 Combine like terms: -69 + -40 = -109 25n = -109 Divide each side by '25'. n = -4.36 Simplifying n = -4.36
| 1+0.036(175/365)= | | 6x+6=4x+4 | | u+4=12 | | (.66x+x)*2=220 | | 7-12=5 | | -2=x-12 | | 7+3k-12=25 | | 7-12= | | 3x^2-15= | | 7-12/3*4= | | 0.14(y-9)+0.10y=0.04y-0.01(60) | | 60k+80=50k+120 | | 10(6)= | | 7-(-60)= | | 6-5(2m-3)=-29 | | -6(2x-3)+15=19 | | 2.5t+6=10t+24 | | (2x+5)=-2 | | 2x-(3y-(4x-(5y-(6x-7y))))= | | 6g+20=2g+36 | | 4y+19=2y+10 | | 2x+3-5(x+1)=6x+5 | | 180=2x+(x+10)+(2x-30) | | [x]=10 | | 3-5(7y-11)= | | 0.14(y-9)+0.10=0.04y-0.01(60) | | x+189326=12 | | 6x^2=-24 | | -4(3x-1.5)+7=39 | | 50+(2x-4)=90 | | -1(x-9)+4x= | | 10-5x=55 |